Tertiary mathematics students: Why are they here? - Forgasz, Helen J.; Leder, Gilah C. (NOMAD Nordic Studies in Mathematics Education, 1998)
This paper is concerned with factors influencing students' decisions to attend university, to study mathematics at university and at school, and their levels of enjoyment of mathematicsin thesesettings.The sample comprised just under 1900 students from five universities. All were enrolled in mathematics subjects. Generally, fewer students liked mathematics at university than at school. Many chose mathematics to keep their options open or because mathematics was a pre-requisite for further study, rather than because of family advice or university publicity. Comparisons were also made between the responses of younger and mature age students, and between females and males.